Desafios ao encontro: contribuições de Moreno e Freire para a educação de jovens e adultos - Silva Amaral, Mara Solange da; Costa-Renders, Elizabete Cristina (Revista Brasileira de Psicodrama, 2020)
The schooling process of teachers of the Youth and Adult Education shows multiple challenges in its daily life: socioeconomic issues, issues of public health and well-being, cognitive and relationship issues. It also carries all the historical legacy of combating illiteracy, social inequalities, and fragility of the public educational policies of this type of education. In this challenging scenario, theoretical approaches between Jacob Levy Moreno and Paulo Freire contribute to a critical reading of limit situations present in daily teaching. Sociodrama, as a method of this research, points to spontaneity-creativity as a possibility for overcoming the dense cultural conserves installed and the possibility of the Encounter.